Necessity of suction drains in gynecomastia surgery - Keskin, Mustafa; Sütçü, Mustafa; Çiğsar, Bülent; Karacaoğlan, Naci (SAGE Publications Inc., 2014)
Background: The aim of gynecomastia surgery is to restore a normal chest contour with minimal signs of breast surgery. Objective: The authors examine the rate of complications in gynecomastia surgery when no closed-suction drains are placed. Methods: One hundred thirty-eight consecutive male patients who underwent gynecomastia surgery without drains were retrospectively analyzed to determine whether the absence of drains adversely affected patient outcomes. Patients were managed by ultrasonic-assisted liposuction both with and without the pull-through technique. Results: The mean age of the patients was 29 years, and the mean volume of breast tissue aspirated was 350 mL per beast. Pull-through was needed in 23 cases. There was only 1 postoperative hematoma. Conclusions: These results are comparable with previously published data for gynecomastia surgery in which drains were placed, suggesting that the absence of drains does not adversely affect postoperative recovery. Routine closed-suction drainage after gynecomastia surgery is unnecessary, and it may be appropriate to omit drains after gynecomastia surgery.
Keywords: Breast Surgery; Complications; Drains; Gynecomastia; Hematoma; Suction